Intrinsically disordered domain of transcription factor TCF-1 is required for T cell developmental fidelity - Goldman, Naomi; Chandra, Aditi; Johnson, Isabelle; Sullivan, Matthew A.; Patil, Abhijeet R.; Vanderbeck, Ashley; Jay, Atishay; Zhou, Yeqiao; Ferrari, Emily K.; Mayne, Leland; Aguilan, Jennifer; Xue, Hai-Hui; et al. (Nature immunology, 2023)
In development, pioneer transcription factors access silent chromatin to reveal lineage-specific gene programs. The structured DNA-binding domains of pioneer factors have been well characterized, but whether and how intrinsically disordered regions affect chromatin and control cell fate is unclear. Here, we report that deletion of an intrinsically disordered region of the pioneer factor TCF-1 (termed L1) leads to an early developmental block in T cells. The few T cells that develop from progenitors expressing TCF-1 lacking L1 exhibit lineage infidelity distinct from the lineage diversion of TCF-1-deficient cells. Mechanistically, L1 is required for activation of T cell genes and repression of GATA2-driven genes, normally reserved to the mast cell and dendritic cell lineages. Underlying this lineage diversion, L1 mediates binding of TCF-1 to its earliest target genes, which are subject to repression as T cells develop. These data suggest that the intrinsically disordered N terminus of TCF-1 maintains T cell lineage fidelity. The DNA-binding domains of transcription factors have been well characterized, but whether their intrinsically disordered regions control cell fate is unclear. Here, the authors show the functional and mechanistic importance of an intrinsically disordered region of TCF-1 in T cell development.